Extreme obesity in the ICU - Joseph Varon; Najia Husaini (World Nutrition Journal, 2022)
Morbid obesity remains an extremely serious disorder resulting in significant impairment of health all over the World. This is particularly true especially now in the setting of lockdowns and people not exercising due to the recent COVID-19 pandemic. In general, overweight and obese adults are at in increased risk of morbidity and mortality from many acute and chronic medical conditions, including hypertension, dyslipidemia, coronary heart disease, diabetes mellitus, gallbladder disease, respiratory disease, some types of cancer, gout and arthritis. Although body weight that exceeds ideal standards as determined by age, sex and height may be accounted for by a greater muscle mass or bone mass, the majority of individuals who weigh more than 20% over their calculated ideal body weight (IBW) have excessive adipose mass. What is even more alarming is the fact that the incidence of obesity in the USA has increased progressively since 1960, when the first survey was conducted. More recent data has demonstrated that the prevalence of obesity is three times higher in the USA than France, and one-and-a-half times that of England. As obesity is such a pervasive disorder in our society, and because obesity is an important risk factor for many diseases, it is not surprising that many obese patients are treated in the intensive care unit (ICU).